(untitled) (Journal of Parents and Teachers, 2014)
Jorge Cela is the International Coordinator of “Fe y Alegría”, the organization that published the book by Rosa María Torres titled 12 thesis for educational change. This article presents the interview with Jorge Cela in which the current world educational situation is analyzed and he also proposed some of the lines of action that aim to achieve "Educational Justice and Economic Justice”.